Evaluation of Chronic Central Serous Chorioretinopathy Treatment at Dr. Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia - Puranto Budi Susetyo; Gitalisa Handayani; Ari Djatikusumo; Anggun Rama Yudantha; Mario Mabuaran Hutapea; Andi Arus Victor (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: Central serous chorioretinopathy (CSC) is a condition characterized by the accumulation of transparent fluid in the posterior pole of the fundus. Currently, there are several therapeutic options that can be used to treat chronic CSC. This study aimed to describe the clinical characteristics and results of the management of chronic CSC. Methods: The design of this study was a descriptive study. This research was conducted at the division of vitreoretina, department of ophthalmology, Faculty of Medicine, Universitas Indonesia, Dr. Cipto Mangunkusumo National General Hospital (RSCM), Jakarta, Indonesia, from April to June 2022. The inclusion criteria were newly diagnosed patients with chronic CSC in the specified period. Data analysis in this study was carried out using descriptive statistics. Snellen vision in patients is converted into logMar vision with the formula-log (decimal vision). Results: There were 17 patients who were included in this study. Among them, 76.4% were men, 52.94% were in the left eye, and there were risk factors for hypertension, as much as 29.41%. Five patients received non-steroidal anti-inflammatory drugs (NSAID) therapy, with 2 of them experiencing increased visual acuity and 3 of them complete resolution. Five patients received anti-VEGF therapy, with 3 of them experiencing increased visual acuity and also complete resolution. Seven patients received subthreshold laser therapy, with all experiencing increased visual acuity, and 4 of them complete resolution. There were 15 patients with subretinal fluid and 2 patients with subretinal fluid combined with retinal pigment epithelial detachment. Conclusion: Most of the patients were male, with an average age of 45.8 years. Most CSC patients affect one eye and still have fairly good vision. The treatments received by patients consisted of non-steroidal anti-inflammatory drugs (NSAID) therapy, anti-VEGF therapy, and subthreshold laser therapy.